Behavioral security: Investigating the attitude of nursing students toward security concepts and practices - Daskalakis, Stelios; Katharaki, Maria; Liaskos, Joseph; Mantas, John (Certification and Security in Health-Related Web Applications: Concepts and Solutions, 2010)
Information and computer security are gaining continuous attention in the context of modern organizations across all domains of human activities. Emphasizing on behavioral factors toward the applicability of security measures and practices is an area under research, aiming to look beyond the strict technical peculiarities and investigate human attitudes in regards to security consciousness and familiarity. The aim of this chapter is to shed light on those aspects in relation with healthcare, by empirically assessing the intention of undergraduate nursing students to apply security concepts and practices. A research theoretical framework is proposed based on an empirical synthesis of constructs adopted from well established theories as the Health Belief Model and the Protection Motivation Theory along with a variety of previous research works. The model is then empirically tested and validated against a sample of 149 undergraduate nursing students. Data analysis was performed using partial least squares. The research findings highlighted the significant effects of perceived benefits, general security orientation and selfefficacy to behavioral intention along with the positive effect of general controllability to self-efficacy of nursing students in applying security concepts and practices, whereas a series of other constructs did not prove to be significant. The study outcomes contribute to further observations related with behavioral security. Despite the fact that the current empirical study was conducted under a specific context and settings, implications are discussed, regarding the security readiness of nursing students prior their engagement to a real healthcare environment. © 2011, IGI Global.